Islamic Social Reporting; Investment Account Holder; Non-Performing Financing; Islamic Corporate Governance; and Maqashid Shariah Index - Faisal, Yusuf; Luthfiyah, Qonitatun; Gumala Sari, Egi (LPPM Universitas Terbuka, 2024)
This study aims to examine, analyze, and obtain empirical evidence regarding the effect of Investment Account Holders, Non-Performing Financing, Islamic Corporate Governance, and the Maqashid Sharia Index on Islamic Social Reporting of the Largest Islamic Banks in the World. This study uses secondary data in the form of annual reports or sustainability reports and other information on Islamic Banks. The samples in this study were the 10 Largest Islamic Banks in the World selected using a purposive sampling technique. The research implementation time was for 6 periods from 2017 - 2022. Research using panel data with panel regression models and data processing software using Eviews. From the results of the study, it is known that only the Islamic Corporate Governance variable significantly affects Islamic Social Reporting, while other variables, namely Investment Account Holder, Non-Performing Financing, and Maqashid Sharia Index do not significantly affect Islamic Social Reporting. This research is expected to provide information related to Islamic social reporting and provide benefits in making the right decisions and can be used as a reference for further research.